2000
DOI: 10.1614/0890-037x(2000)014[0122:paapio]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Palmer Amaranth (Amaranthus palmeri) Impacts on Yield, Harvesting, and Ginning in Dryland Cotton (Gossypium hirsutum)1

Abstract: The impact of Palmer amaranth on mechanical harvesting, ginning, and fiber quality in dryland cotton was documented. Only the highest Palmer amaranth density (3,260 weeds/ha) reduced lint and seed yields. However, all weed densities increased harvesting time 2- to 3.5-fold. Two factors increased the time required for stripper harvesting: slower ground speeds due to large weeds and work stoppages that required hand removal of weed stems lodged in the harvester. Ninety-eight percent of the weedy plant material w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
84
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 7 publications
4
84
0
1
Order By: Relevance
“…In spite of the effect of Palmer amaranth on lint quantity, cotton fiber qualities (i.e. micronaire, length, strength, and color) were not affected by Palmer amaranth weed density (Morgan et al 2001;Rowland et al 1999;Smith et al 2000).…”
Section: Agricultural Impacts Of Palmer Amaranthmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the effect of Palmer amaranth on lint quantity, cotton fiber qualities (i.e. micronaire, length, strength, and color) were not affected by Palmer amaranth weed density (Morgan et al 2001;Rowland et al 1999;Smith et al 2000).…”
Section: Agricultural Impacts Of Palmer Amaranthmentioning
confidence: 99%
“…Morgan et al (2001) concluded that mechanical harvest was impractical because of potential equipment damage once Palmer amaranth densities were in excess of 0.65 plants m À2 (six plants 9.1 m À1 row). Fields infested with Palmer amaranth resulted in cotton lint that contained up to 15% trash, but the residual weed matter was successfully removed using a lint cleaner, though there is an additional cost associated with this practice (Smith et al 2000). In spite of the effect of Palmer amaranth on lint quantity, cotton fiber qualities (i.e.…”
Section: Agricultural Impacts Of Palmer Amaranthmentioning
confidence: 99%
“…In addition to reducing yields, the large amounts of biomass produced by mature Palmer amaranth plants interfere with cotton harvest, compromising harvest efficiency by the frequency of work stoppages needed to dislodge thick Palmer amaranth plant stems from harvest equipment (Smith et al 2000). The presence of Palmer amaranth increased harvest time between two-to four-fold, relative to the weedfree control (Smith et al 2000).…”
Section: Agricultural Impacts Of Palmer Amaranthmentioning
confidence: 99%
“…The presence of Palmer amaranth increased harvest time between two-to four-fold, relative to the weedfree control (Smith et al 2000). Morgan et al (2001) concluded that mechanical harvest was impractical because of potential equipment damage once Palmer amaranth densities were in excess of 0.65 plants m À2 (six plants 9.1 m À1 row).…”
Section: Agricultural Impacts Of Palmer Amaranthmentioning
confidence: 99%
“…It can emerge beneath sparse crop canopies (Jha et al 2006), characteristic of crops grown in wide rows. Because Palmer amaranth can grow at rates exceeding 3.5 cm per day and reach heights in excess of 2 m (Garvey 1999;Norsworthy et al 2008b), it quickly overtops slower-growing crops such as cotton, reducing lint yield up to 92% (Rowland et al 1999) and lowering harvest efficiency (Smith et al 2000).…”
mentioning
confidence: 99%